Pengaruh Pendapatan Asli Daerah dan Dana Alokasi Umum pada Belanja Daerah dengan Variabel Independen Produk Domestik Regional Bruto dan Jumlah Penduduk dalam Pengujian Hipotesis Flypaper Effect pada Pemerintah Kota/Kabupaten di Jawa Timur Tahun 2015-2024 - Akhmad Febriansyah; Henryanto Wijaya (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
East Java Province has one of Indonesia’s largest fiscal structures, marked by increasing Regional Expenditure from 2015 to 2024, though dependency on central transfers like the General Allocation Fund (DAU) remains significant. This study aims to analyze the effects of Local Revenue (PAD), DAU, Gross Regional Domestic Product (GRDP), and Population on Regional Expenditure across East Java’s regencies and cities, and to determine the presence of the Flypaper Effect before and after the COVID-19 pandemic. Using secondary data from BPS and regional financial reports, the analysis employs a panel data regression with the Fixed Effect Model (FEM) determined through Chow, Hausman, and LM tests. Results show that PAD, DAU, GRDP, and Population significantly influence Regional Expenditure simultaneously. Partially, PAD is the most significant factor, while DAU is only significant at the 10% level. The study finds no Flypaper Effect in either period, concluding that fiscal dependency patterns have shifted toward greater local fiscal autonomy.